2019
DOI: 10.1109/access.2019.2910323
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Investigation on the Effects of Ambient Freeze–Thaw Cycling on Creep Mechanical Properties of Sandstone Under Step Loading

Abstract: In order to study the creep mechanical properties of sandstone subjected to graded loading under the condition of freeze-thaw cycles, 15 freeze-thaw cycles were conducted with four groups of rock samples. The porosity variation of sandstone before and after the freeze-thaw cycles were obtained by using the nuclear magnetic resonance (NMR) technique. The results show that under the action of freeze-thaw cycles, the cohesion between particles inside the rock decreases, the pore structure deteriorates continuousl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 20 publications
0
4
0
Order By: Relevance
“…Yang et al [ 18 ] analyzed the microstructure damage to quartz sandstone under the coupling effect of water and freeze–thaw cycles using a scanning electron microscope [ 19 ]. Li et al [ 20 ] obtained the T 2 spectrum distribution and porosity variation of sandstone before and after freeze–thaw cycles using the nuclear magnetic resonance (NMR) technique. Liu et al [ 21 ] used three-dimensional digital technology to study the change in the micropore structure of water-rich sandstone during freeze–thaw cycles and found that the freeze–thaw degradation mainly manifested in the increase in small pore size.…”
Section: Introductionmentioning
confidence: 99%
“…Yang et al [ 18 ] analyzed the microstructure damage to quartz sandstone under the coupling effect of water and freeze–thaw cycles using a scanning electron microscope [ 19 ]. Li et al [ 20 ] obtained the T 2 spectrum distribution and porosity variation of sandstone before and after freeze–thaw cycles using the nuclear magnetic resonance (NMR) technique. Liu et al [ 21 ] used three-dimensional digital technology to study the change in the micropore structure of water-rich sandstone during freeze–thaw cycles and found that the freeze–thaw degradation mainly manifested in the increase in small pore size.…”
Section: Introductionmentioning
confidence: 99%
“…Since freeze-thaw controls the phase change process of pore water by adjusting the temperature, some scholars have tried to reveal the freeze-thaw damage mechanism from a meso-level perspective [ 7 , 8 , 9 , 10 , 11 ]. For example, Liu et al [ 12 ] used CT scanning technology to detect the damage characteristics of rock meso-structure, and achieved a quantitative description of freeze-thaw damage.…”
Section: Introductionmentioning
confidence: 99%
“…They combined these results with the fractal theory to explore the influence of freezing temperature and freeze thaw cycling time on pore structure variation in silty clay. Li et al performed fifteen freeze thaw cycles on four groups of sandstone samples under graded loading while measuring the pore variation via nuclear magnetic resonance (NMR) and studying their creep mechanical properties [7]. The results demonstrated decreased cohesion between the rock particles, deteriorated pore structure, and increased porosity after freeze thaw cycling.…”
Section: Introductionmentioning
confidence: 99%